2008
DOI: 10.1186/1757-2215-1-3
|View full text |Cite
|
Sign up to set email alerts
|

ST6Gal-I expression in ovarian cancer cells promotes an invasive phenotype by altering integrin glycosylation and function

Abstract: Background: Ovarian adenocarcinoma is not generally discovered in patients until there has been widespread intraperitoneal dissemination, which is why ovarian cancer is the deadliest gynecologic malignancy. Though incompletely understood, the mechanism of peritoneal metastasis relies on primary tumor cells being able to detach themselves from the tumor, escape normal apoptotic pathways while free floating, and adhere to, and eventually invade through, the peritoneal surface. Our laboratory has previously shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
95
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(101 citation statements)
references
References 41 publications
4
95
0
Order By: Relevance
“…this increased negative charged properties of sialic acids was correlated with reduced adhesiveness of tumor cells and may be suitable for conformational change of integrin and enhances its function in cell-ecM interactions (33). similar studies have also indicated that increased sialylation could activate β1 integrin, mediate its adhesion to ecM proteins (34) and stimulating cell migration through host ecM (35). Most of these studies and our finding supported the hypothesis that increase of sialylation of cancer cells play an important role in tumor metastasis.…”
Section: Discussionmentioning
confidence: 79%
“…this increased negative charged properties of sialic acids was correlated with reduced adhesiveness of tumor cells and may be suitable for conformational change of integrin and enhances its function in cell-ecM interactions (33). similar studies have also indicated that increased sialylation could activate β1 integrin, mediate its adhesion to ecM proteins (34) and stimulating cell migration through host ecM (35). Most of these studies and our finding supported the hypothesis that increase of sialylation of cancer cells play an important role in tumor metastasis.…”
Section: Discussionmentioning
confidence: 79%
“…6). Indeed, elevated levels of ST6GAL1 and ␣2,6-sialylation have been observed in several types of tumors, including colon cancer (18,52) and ovarian cancer (42,53). The expression levels of ST6GAL1 mRNA and enzyme activities are known to be particularly enhanced in metastatic tumors, which were promoted by the Ras oncogene (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown Cells-Many studies have suggested that sialylation played a crucial role in integrin-mediated cell migration (18,20,42). To clarify the relationships between GOLPH3 and sialylation, as described above, we overexpressed an shRNAresistant GOLPH3 gene in the GOLPH3-knockdown cells and then examined cell migration and N-glycan structures.…”
Section: Restoration Of Golph3 Expression Rescued the Sialylation Andmentioning
confidence: 99%
“…There have been several reports indicating that changes in sialylation patterns correlate with changes in cell motility and invasiveness [44][45][46][47]. In melanoma, it has been shown that adhesion molecules such as N-cadherin and integrins undergo altered glycosylation and sialic acid modification [48][49][50][51].…”
Section: Sialylation In Pmelmentioning
confidence: 99%